Computational investigation of the atmospheric oxidation reactions of polybrominated dibenzo-p-dioxins initiated by OH radicals. (December 2018) - Zeng, Xiaolan; Wang, Yan
Abstract: Density functional theory (DFT) method was used to study OH-initiated atmospheric oxidative reactions of some polybrominated dibenzo- p -dioxins (PBDDs). B3LYP functional and 6–311++G (2df, p) basis set were applied to optimize molecular structures of all stationary points involved in the investigated reactions. The rate constants for key elementary reactions were estimated by means of transition state theory. The computational results demonstrate that all addition reactions of PBDDs with OH radicals can occur spontaneously at standard conditions, however, the OH addition reactions are very slow due to low atmospheric concentration of OH radicals. Addition reactions occurring at γ-C position dominate in OH addition of all PBDDs. With the number of bromine atoms substituting at α-sites increases, the overall rate coefficients of OH addition decrease. The succeeding addition reactions of PBDD-OH adducts with O2 take place hardly both thermodynamically and kinetically. Abstraction reaction of H atoms by O2 is a governing route for PBDD-α(β)-adducts without bromine atoms at the same site, while the fused-ring CO bond fission is a main reaction channel for PBDD-γ-adducts, which will produce substituted phenoxy radicals. Highlights: We studied OH-initiated atmospheric degradation mechanisms of PBDDs theoretically. OH addition reactions occurring at γ-C positions of PBDDs dominate. Bromination at α-C atoms of PBDDs inhibits OH addition reactions kinetically. Addition reactions of O2 to PBDD-OH adducts are difficult to occur thermodynamically. Phenoxy radicals are predominant products for oxidative degradation of PBDDs.